PENGARUH INTRINSIC MOTIVATION, PERCEIVED AUTONOMY SUPPORT, DAN JOB CRAFTING TERHADAP INNOVATIVE WORK BEHAVIOR DI TK-SD XYZ TANGERANG SELATAN [THE IMPACT OF INTRINSIC MOTIVATION, PERCEIVED AUTONOMY SUPPORT, AND JOB CRAFTING TOWARD INNOVATIVE WORK BEHAVIOR IN TK-SD XYZ SOUTH TANGERANG] - Margaretha M.B., Junita; Sudibjo, Niko (Universitas Pelita Harapan, 2024)
The world of education is very dynamic. Teachers, as the frontliners of education, are expected to keep up with the times. 21st century skills are believed to be essential to be integrated and implemented for the success of students and teachers. One of the 21st century skills taken as the basis of this research is innovation. Innovative work behavior is a continuous process that starts with seeking opportunities for ideas to solve problems encountered, then developing those ideas in new or alternative ways so that they can be accepted in the organization and implemented to provide benefits to both performance and the organization. This study aims to see the effect of intrinsic motivation, perceived autonomy support, and job crafting on innovative work behavior in XYZ Early Childhood Years and Elementary School, South Tangerang. Data were obtained from 80 Early Childhood Years and Elementary School teachers by using online questionnaires. This research is quantitative research using the path analysis through SEM-PLS method. The results of this study indicate that intrinsic motivation, perceived autonomy support, and job crafting have positive effect on innovative work behavior.Bahasa Indonesia AbstrakDunia pendidikan sangatlah dinamis. Sebagai pelaksana dan ujung tombak pada dunia pendidikan, guru diharapkan untuk dapat mengikuti perkembangan zaman. Keterampilan abad 21 diyakini penting untuk diintegrasikan dan diimplementasikan bagi kesuksesan para siswa dan guru. Salah satu keterampilan abad 21 yang diambil sebagai dasar penelitian ini adalah inovasi. Innovative work behavior adalah suatu perilaku yang berkelanjutan, yang dimulai dari pencarian peluang ide untuk memecahkan masalah yang dihadapi, lalu dikembangkan dengan cara-cara baru atau alternatif sehingga dapat diterima dalam organisasi dan diimplementasikan untuk memberikan keuntungan atau manfaat kepada kinerja maupun organisasi. Penelitian ini bertujuan untuk melihat pengaruh intrinsic motivation, perceived autonomy support, dan job crafting terhadap innovative work behavior di TK-SD XYZ Tangerang Selatan. Data diperoleh dari 80 guru di TK-SD tersebut dengan cara penyebaran kuesioner secara daring. Penelitian ini adalah penelitian kuantitatif dengan analisis jalur melalui metode SEM-PLS. Hasil penelitian ini menunjukkan bahwa intrinsic motivation, perceived autonomy support, dan job crafting berpengaruh positif terhadap innovative work behavior.